Chase's calendar of events 2020 the ultimate go-to guide for special days, weeks and months - Chase's, Editors of (Lanham Bernan press, 2019)
"Since 1957, Chase's Calendar of Events lists everything worth knowing and celebrating for each day of the ear: 12,500 holidays, historical milestones, famous birthdays, festivals, sporting events and much more. "The Oxford English Dictionary of holidays." NPR's Planet Money"--Provided by publisher.
Keywords: Holidays; Calendars; Festivals; Chronology; Anniversaries; Almanacs; Directories